2016
DOI: 10.1123/jpah.2015-0539
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Trends of Finnish Adolescents With Long-Term Illnesses or Disabilities From 2002–2014

Abstract: Background:Adolescents’ physical activity level is a major source of concern. For adolescents with long-term illnesses or disabilities (LTID), being physically active can prevent secondary conditions. This is one of the first studies reporting trends in physical activity of adolescents with LTID in relation to gender, age, and sports club membership.Methods:Data were collected from the Health Behavior in School-aged Children study in Finland during 2002, 2006, 2010, and 2014. In 13- and 15-year-olds (N = 2206)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…However, the differences were not strong enough to influence the statistical model. This concurs with previous studies from mainstream school populations whereby there were no significant differences in PA levels between adolescents with and without disabilities [58,59]. In this study, the differences among the various functional differences were not reported neither since, of all the different functional difficulty categories, only adolescents with moving difficulties were significantly less active than other adolescents [60].…”
Section: Discussionsupporting
confidence: 92%
“…However, the differences were not strong enough to influence the statistical model. This concurs with previous studies from mainstream school populations whereby there were no significant differences in PA levels between adolescents with and without disabilities [58,59]. In this study, the differences among the various functional differences were not reported neither since, of all the different functional difficulty categories, only adolescents with moving difficulties were significantly less active than other adolescents [60].…”
Section: Discussionsupporting
confidence: 92%
“…The term sports club is synonymous with organized sport and both are considered to consist of environments that support the healthy behaviours of its athletic members [2]. For example, sports club members have a good nutritional intake [3] and more meet physical activity recommendations than their non-members peers [4]. In addition to improved physical health, other non-sport specific psychosocial objectives, such as promoting social development, belonging and friendship, can be met through sports club participation [5].…”
Section: Introductionmentioning
confidence: 99%
“…In other research, non-organised sports produces nearly twice as many injuries as in the organised sports setting (Zaricznyj et al 1980), and this may be an incentive for people at risk of injuries to attend sports clubs rather than to pursue their own activities as recent trends have shown (Ng et al 2016b). Sport clubs have a responsibility to adhere to safety promotion guidelines.…”
Section: Discussionmentioning
confidence: 96%
“…Adding to the literature, in Ramirez’s study (Ramirez et al 2009), the researchers followed special education interscholastic league for the course of a season. In recent years, there has been an increase in overall PA in adolescents with LTID (Ng et al 2016b) and the amount of activities targeted for children that attend special education in Finland (Mononen et al 2014). However, studies like these often fail to report whether children that attend these activities are part of the mainstream school system, hence providing addition information to this phenomena.…”
Section: Discussionmentioning
confidence: 99%